SINTESIS NANOPARTIKEL PERAK MENGGUNAKAN EKSTRAK DAUN PAKIS (Stenochlaena sp.) SEBAGAI BIOREDUKTOR - Yuniarsih, Dwi; Gusrizal, Gusrizal; Alimuddin, Andi Hairil (Tanjungpura University, 2025)
The use of biological reductants has been identified as a more environmentally friendly approach in nanoparticle synthesis than the use of chemical reductants, which can produce hazardous waste. The aims of this study were synthesize silver nanoparticles using fern leaf extract (Stenochlaena sp.) as a bioreductor and stabilizing/protecting agent, as well as to test the stability of the resulting silver nanoparticles and perform characterization. Synthesis of silver nanoparticles involves the reaction of a silver nitrate solution with a fern leaf extract solution in boiling water. Stability of the silver nanoparticles as observed over a period of one month indicated a decline in stability. FTIR spectrum analysis demonstrated indicating a direct involvement of the extract in the reduction process as well as the presence of Ag-O bonds in the FTIR spectrum of silver nanoparticles. TEM analysis revealed that the size of the silver nanoparticles ranged from 3 to 16 nanometers, with a relatively spherical morphology. PSA demonstrated that the silver nanoparticles had a zeta potential value of +12.7 mV. This study offers insight into the potential of fern leaf extract as a bioreductor in the synthesis of silver nanoparticles and the physical chemical characteristics of the resulting nanoparticles.